Pakistan’s Influence on Sino-Indian Relations in Geo-strategy and Security - Xing, Bowei (Transactions on Social Science, Education and Humanities Research, 2023)
In this paper, I analyze Pakistan’s Influence on Sino-Indian Relations in geopolitics and security, economy, and military. In my dissertation, my point is that Pakistan has affected Sino-Indian relations in many ways. This impact should not be simply attributed to positive or negative impact. In fact, Pakistan’s role in Sino-Indian relations is diversified. The instability in Pakistan and the Sino-Pakistani relations have exacerbated the mutual suspicion between China and India, but also provided new ideas for Sino-Indian cooperation. I use realism, liberalism and constructivism at the same time to explain my research problems. Moreover, I have integrated many new theories and viewpoints in recent years and the recent events between China, India and Pakistan into my research.